Pengaruh Pengalaman Lapangan Industri (PLI) dan Kesiapan Mental terhadap Employability Skill: Mediasi Pemahaman Dunia Kerja Mahasiswa Tata Rias dan Kecantikan FPP UNP - Ayda Murni; Indra Saputra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research was initiated due to concerns regarding the low employability skills among vocational education graduates. A number of contributing factors have been identified, such as limited exposure to industrial field experience, insufficient mental preparedness, and a lack of comprehensive understanding of the professional work environment. The aim of this study is to investigate the extent to which industrial field experience and mental readiness impact employability skills, with the understanding of the world of work serving as a mediating variable. A quantitative research design was employed, utilizing the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, which is well-suited for analyzing complex relationships among latent variables, particularly when the data does not meet the assumption of normality and involves multiple indicators. The results demonstrate that industrial field experience (PLI), mental preparedness, and understanding of the world of work significantly affect the employability skills of students in the Cosmetology and Beauty Study Program. In addition, the understanding of the world of work was found to significantly mediate the effects of both industrial field experience and mental preparedness on students' employability outcomes